Barriers and facilitators for the implementation of delayed-prescription of antibiotics in family medicine: a qualitative study - Aline Rinaldi; Serena Petrocchi; Luca Gabutti; Anna Bullo; Peter Johannes Schulz (BMC Health Services Research)
Abstract Background Delayed prescription is a strategy used in various countries to reduce antibiotic overuse and contend the effects of antibiotic resistance; however this practice is not yet used in Switzerland. The present qualitative study was thus conducted to investigate Swiss patients’ attitudes towards the possible implementation of delayed prescription. Method Five focus groups with the general population based on a fixed script of questions to elicit opinions on delayed prescription. Results A total of 29 participants were involved (M = 39,76 years of age, SD = 15,91; 19 females). Participants naturally polarized into two distinct groups: one expressing attitudes against delayed prescription and the other in favor of such practice. One driver for their opposing stance was their pre-existing negative attitudes about the use of antibiotics. Other relevant themes contributing to the formation of one’s opinion on delayed prescription included the participants’ perceived convenience of this prescribing practice and their desired level of autonomy during and after a medical encounter. Another theme that emerged was the potential impact of these stances on the interpersonal relationship between doctors and their patients. Conclusion The present study highlights the existence of several barriers and facilitators perceived by patients. Should delayed prescription be implemented in Switzerland, these results will inform policymakers about patients’ attitudes towards the practice. Doctors may also benefit from this study as it identifies the limitations to consider when discussing treatment options with patients.